Аналіз видів корпоративних мереж - Скорик, Ю. В.; Плех, О. А. (ХНУРЕ, 2025)
This work analyzes the types of corporate networks, namely departmental networks and campus networks. The advantages and disadvantages of corporate networks are considered. Departmental networks effectively connect and coordinate the work of individual departments, while campus networks integrate larger geographically dispersed structures, creating a single information system for the company. Both types of networks increase productivity, help optimize business processes, and provide reliable communication across the enterprise.
Keywords: види корпоративних мереж; корпоративна мережа